2017
DOI: 10.1021/acs.biochem.6b01304
|View full text |Cite
|
Sign up to set email alerts
|

The Iron Chaperone Protein CyaY from Vibrio cholerae Is a Heme-Binding Protein

Abstract: CyaY is an iron transport protein for iron-sulfur (Fe-S) cluster biosynthetic systems. It also transports iron to ferrochelatase that catalyzes insertion of Fe into protoporphyrin IX. Here, we find that CyaY has the ability to bind heme as well as iron, exhibiting an apparent dissociation constant for heme of 21 ± 6 nM. Absorption and resonance Raman spectra revealed that both ferric and ferrous forms of heme were bound to an anionic ligand (e.g., tyrosine and/or cysteine). Consistent with this, mutagenesis st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…Heme-induced oligomerization has been reported in some proteins. , The oligomerization status of PBGD was next evaluated using a gel filtration column to confirm whether quaternary structural changes occurred upon heme binding. In the absence of heme, PBGD was eluted at 24.0 mL (Figure B).…”
Section: Resultsmentioning
confidence: 99%
“…Heme-induced oligomerization has been reported in some proteins. , The oligomerization status of PBGD was next evaluated using a gel filtration column to confirm whether quaternary structural changes occurred upon heme binding. In the absence of heme, PBGD was eluted at 24.0 mL (Figure B).…”
Section: Resultsmentioning
confidence: 99%
“…Although in vitro results, specially when protein-protein interactions and protein oligomerization are concerned, are not always easy to verify directly in living cells, it still should be possible to link the findings to processes observed in vivo . As noted in the introduction, one of the primary functions of CyaY is related to its involvement in the ISC assembly machinery [ 19 , 61 ], but also in heme synthesis [ 20 ], and presumably in the regulation of ISC assembly [ 21 ]. In addition, heme biding appears to induce oligomerization of the protein, although the type of the oligomers is not known.…”
Section: Discussionmentioning
confidence: 99%
“…CyaY from Bacilus subtilis has also been shown to interact with ferrochelatase, the terminal enzyme of heme synthesis that catalyzes iron insertion into protoporphyrin IX [ 20 ]. In addition, it was shown that Vibrio cholerae CyaY binds heme with dissociation constant in the nano-molar range [ 21 ], and that heme biding induced oligomerization of the protein. The authors suggest that heme binding to CyaY serves in the regulation of ISC assembly and may facilitate iron transfer to both the ISC assembly complex and to ferrochelatase.…”
Section: Introductionmentioning
confidence: 99%
“…No pH changes in the medium were observed after the addition of hemin solution. Absorbance differences at 404-409 nm were plotted as a function of heme concentration, and apparent dissociation constants (K d,heme ) calculated using a quadratic binding equation [35].…”
Section: Measurement Of Heme Binding To Hutzmentioning
confidence: 99%
“…The inactivation of Arg92 mutants can be accounted for slow protonation of the reduced oxyferrous heme, as discussed below. The reaction mechanism of heme degradation by HutZ was previously determined [35] (Supplemental Fig. S2).…”
Section: Inactivation Mechanism Of Heme-arg92 Mutantsmentioning
confidence: 99%